Comprehensive evaluation of some phagocytosis parameters in children aged 2-5 years, depending on the incidence of acute respiratory infections - O.V. Tymoshyna; L.S. Ovcharenko; A.O. Vertehel; I.V. Samokhin; O.V. Kryazhev (Zaslavsky O.Yu., 2023)
Background. After respiratory virus infection, there is an increased production of pro-inflammatory cytokines, including tumor necrosis factor (TNF) α, interleukin (IL) 6, IL-1β that leads to cross-activation of the neuroendocrine immune system, which can impair phagocytosis with an increase in the incidence of upper respiratory tract infections (URTI), forming a vicious circle. The aim: to increase the effectiveness of diagnosing immune disorders in children aged 2-5 years with recurrent URTI by means of a comparative analysis of data obtained based on the study of some parameters of phagocytosis, serum levels of pro-inflammatory cytokines and lipid peroxidation products. Materials and methods. Sixty children aged from 2 to 5 years were under observation, two groups were formed: 1) patients with recurrent URTI (n = 30); 2) children who suffer from URTI less than 6 times a year (n = 30). Results. The children of group 1 had increased frequency of registration of low indicators of the phagocytic number (by 60.0 %, p < 0.05), phagocytic index (by 56.0 %, p < 0.05), and the index of completion of phagocytosis (by 70.0 %, p < 0.05), Staphylococcus-stimulated nitroblue tetrazolium test (by 50.0 %, p < 0.05) and high indicators of spontaneous nitroblue tetrazolium test (by 43.3 %, p < 0.05), high serum levels of IL-1β (by 46.7 %, p < 0.05), IL-6 (by 43.3 %, p < 0.05), IL-10 (by 30.0 %, p < 0.05), TNF-α (by 46.7 %, p < 0.05), an increase in the ratio of IL-6/IL-10 by 2 or more times, high levels of lipid hydroperoxides (by 80.0 %, p < 0.05), diene conjugates (by 80.0 %, p < 0.05), malondialdehyde (by 76.7 %, p < 0.05), diene ketones (by 76.7 %, p < 0.05), Schiff bases (by 76.7 %, p < 0.05). Conclusions. Children aged 2-5 years with recurrent URTI have features of absorptive, cytokine-inducing and metabolic functions of phagocytosis, which was manifested in an increase in the serum concentration of pro-inflammatory cytokines and products of all stages of lipid peroxidation of cell membranes.